(untitled) (Journal of the College of Basic Education, 2022)
Iraq was described as the country with the most restrictions in four reports in a row for the pew forum index from 2009 to 2013 and then rose to 2014, especially against minorities where discrimination frameworks are practiced towards ethnic and cultural minorities as they are rooted in the political history of Iraq since international covenants and regulations The political ruling at that time for its various ideologies to preserve its survival and authority without paying attention to the interests and lives of minorities who are considered the building block and cultural image of the country, As these policies penetrated the mechanisms of implementing the ruling and demonstrated it in the institutions affiliated with the successive regimes represented by the police and the judiciary, whereby it was an executive mechanism for all the aspects that were mentioned. Therefore, contemporary Iraq needs to sow the seeds of the correct democratic system according to social justice for its children, away from the anxious and confusing life of the Iraqi society in all its cultural and religious spectra throughout the previous historical experiences that invaded our country according to a wise democracy that establishes the rights of all as it is in the 2005 constitution, which was made available to Iraqis based on Its paragraphs provide complete freedom for the country of cultural, ethnic and racial diversity for all Iraqis, according to Article 4 of the constitution in which it recognizes the rights of minorities, including freedom to worship and live in peace in all aspects of life, the most important of which is their enjoyment of services and jobs without Leigh or racist